PRELIMINARY STUDIES ON THE IMPACT OF CLIMATE CHANGE ON THE UPWELLING PHENOMENON IN SOUTH CENTRAL VIETNAM WATERS IN SUMMER - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2017)
Recent international studies have demonstrated the decadal variability in the circulation patterns of East Vietnam Sea in the summer with three phases in 1998, 2001 and 2010 respectively. From the analytical results of the sea water level in 20 years, the variation of the water level in the period from 3 - 7 years was considered. Uptrend in regional water levels can be separated into phases 1993-2001, 2007-2010, and the sea water level in the 2002-2005 period remained almost unchanged. Noted that the abnormal increases in the water level in 2001 and 2010 were within the period of La Niña active phase. Obviously, these changes will significantly affect the upwelling of South Central Vietnam. To seek an answer, we have analyzed the data sequence HYCOM + NCODA with 1/12.50 Global Reanalysis. This sequence is quite reliable to assess the scale and the characteristics of ocean eddies with the size of a few tens of kilometers. With this data series, the movement and formation of the eddies can be analyzed, including processes that control the surface mixed layer, the meanders of ocean currents and fronts, the generation and propagation of coastal trapped waves.